Qur'anic Strategy Realizing Couple Harmony in Surah Al-Ahzab Verse 28 - Surur, Aziz Miftahus; Muttaqin, Aris Anwaril (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Research on the Qur'anic strategy in realizing couple harmony needs to be conducted to describe the understanding of the Qur'an in the early days of development with the facts that occur today. The purpose of this study is to present an understanding of the Qur'an that is in accordance with the current context. Knowing the tafsir method offered by Muhammad Sayyid Tantawi about the importance of caring for and maintaining couple relationships. The method used in this study is based on a literature method. This study found that harmony is the main goal of marriage. To realize harmony, several alternatives and solutions are needed for husband-and-wife couples. Surah al-Ahzab verse 28 tells about the challenge of the Prophet Muhammad in dealing with internal family problems. The success of Prophet Muhammad in solving these problems can be used as an alternative to solving the problems faced by every couple. Contribution: This study adapts Muhammad Sayyid Tantawi's interpretation to offer Qur’anic solutions for marital harmony.